How Am I Doing? Perceived Financial Well-Being, Its Potential Antecedents, and Its Relation to Overall Well-Being - Netemeyer, Richard G; Warmath, Dee; Fernandes, Daniel; Lynch, John G (Journal of Consumer Research, 2018)
Abstract Though perceived financial well-being is viewed as an important topic of consumer research, the literature contains no accepted definition of this construct. Further, there has been little systematic examination of how perceived financial well-being may affect overall well-being. Using consumer financial narratives, several large-scale surveys, and two experiments, we conceptualize perceived financial well-being as two related but separate constructs: 1) stress related to the management of money today (current money management stress), and 2) a sense of security in one’s financial future (expected future financial security). We develop and validate measures of these constructs (web appendix A) and then demonstrate their relationship to overall well-being, controlling for other life domains and objective measures of the financial domain. Our findings demonstrate that perceived financial well-being is a key predictor of overall well-being and comparable in magnitude to the combined effect of other life domains (job satisfaction, physical health assessment, and relationship support satisfaction). Further, the relative importance of current money management stress to overall well-being varies by income groups and due to the differing antecedents of current money management stress and expected future financial security. Implications for financial well-being and education efforts are offered.